Third World Tops in South - Unknown (Daily Express)
Trinidad Tesoro Third World of Fyzabad tops the semi-finals at the Southern Steelband Movement Panorama at Skinner Park as steelbands from Point Fortin and Fyzabad stole the spotlight. They were followed by Ross and Sons Antilleans and Point D'Or Nightingales of La Brea. The results of the competition are stated.
Keywords: Steel bands (Music) -- Competitions -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago; Panorama (Musical festival); Steel bands (Music) -- Trinidad and Tobago